A comparative study of Ebola hemorrhagic fever epidemic trends in three West African countries (Guinea, Liberia and Sierra Leone) - Camara, Ansoumane Yassima; Diallo, Lansana Laho; Camara, Moussa Kantara; Camara, Mohamed ElMady; Kouyate, Moustapha; Keita, Sadio; Diawara, Safere; Traore, Falaye (International Journal Of Community Medicine And Public Health, 2017)
Background: From 2014 to 2015, West Africa has faced an unprecedented Ebola outbreak and the most affected three countries were Guinea, Liberia and Sierra Leone. The purpose of this paper was to analyze Ebola cases in these three Countries and compare the epidemic trends in each country. Methods:This study was comparative and covered the period from August 2014 to November 24th 2015. It is based on statistics provided by each country to the World Health Organization (WHO); which are available on the WHO’s website under the title of “situation reports in response to the Ebola outbreak”. The paper analysed the trend of probable, confirmed and death cases in each country, and presented various strategies used. Results: The results shown that combine number of probable and confirmed cases of Ebola virus disease (EVD) was higher in Sierra Leone (8,991 cases) compare to Liberia (5,036 cases) and Guinea (3,804 cases). However, the total number of death was higher in Liberia with 4,808 deaths followed by Sierra Leone with 3,955 deaths, then the Republic of Guinea with 2,536 deaths. Conclusions:We can retain that the West African Ebola outbreak started in Guinea and stayed there longer, but Sierra Leone had the higher number of confirmed Ebola cases, while Liberia had the highest number of deaths. This epidemic highlighted the weaknesses of different health care systems and the lack of epidemiologic surveillance in these countries. The need to implement a sustainable epidemiologic surveillance system has been underlined.